’n Retoriese benadering tot die Nuwe Testament - Brink, H. J. B. (Verbum et ecclesia, 1993)
A rhetorical approach to the New Testament Although a rhetorical approach to the New Testament implies careful attention to certain stylistic features of the text, it also entails a greater awareness of the social dimensions of the interpretation of the Bible. Attention is given to the gradual resurgence of rhetorical studies. The relevance of rhetorical criticism for New Testament studies is also discussed.